2022
DOI: 10.1136/jitc-2021-003416
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive tumor-associated macrophages expressing interlukin-10 conferred poor prognosis and therapeutic vulnerability in patients with muscle-invasive bladder cancer

Abstract: BackgroundTumor-associated macrophages (TAMs) secreting IL-10 could be a specific functional cell subset with distinct polarization state and suppressive role in antitumor immune response. Here, we assessed the associations of clinical outcome, therapeutic responses and molecular features with IL-10+TAMs infiltration, and potential impact of IL-10+TAMs on the immune contexture in muscle-invasive bladder cancer (MIBC).MethodsIn this retrospective study, 128 patients and 391 patients with MIBC from Zhongshan hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…High infiltrations of IL-10 + TAMs cause immune effector cells such as CD8 + T cells and NK cells to be fatigued or dysfunctional, depriving them of their active role in anti-tumor immune responses. IL-10 also suppresses cytotoxic T cell responses by inducing monocytes to express the co-stimulatory molecule PD-L1 and upregulating immune checkpoints, such as CTLA-4, TIM-3, and LAG-3 [ 89 , 90 ]. Serum IL-10 levels have been found to positively correlate with tumor progression; moreover, studies have revealed that IL-10 + TAMs act as a signaling molecule that promotes immune evasion in breast, gastric, and bladder cancers, negatively correlating with overall patient survival and recurrence-free survival [ 90 92 ].…”
Section: Mechanisms Of Tumor Progression Mediated By Macrophagesmentioning
confidence: 99%
See 2 more Smart Citations
“…High infiltrations of IL-10 + TAMs cause immune effector cells such as CD8 + T cells and NK cells to be fatigued or dysfunctional, depriving them of their active role in anti-tumor immune responses. IL-10 also suppresses cytotoxic T cell responses by inducing monocytes to express the co-stimulatory molecule PD-L1 and upregulating immune checkpoints, such as CTLA-4, TIM-3, and LAG-3 [ 89 , 90 ]. Serum IL-10 levels have been found to positively correlate with tumor progression; moreover, studies have revealed that IL-10 + TAMs act as a signaling molecule that promotes immune evasion in breast, gastric, and bladder cancers, negatively correlating with overall patient survival and recurrence-free survival [ 90 92 ].…”
Section: Mechanisms Of Tumor Progression Mediated By Macrophagesmentioning
confidence: 99%
“…IL-10 also suppresses cytotoxic T cell responses by inducing monocytes to express the co-stimulatory molecule PD-L1 and upregulating immune checkpoints, such as CTLA-4, TIM-3, and LAG-3 [ 89 , 90 ]. Serum IL-10 levels have been found to positively correlate with tumor progression; moreover, studies have revealed that IL-10 + TAMs act as a signaling molecule that promotes immune evasion in breast, gastric, and bladder cancers, negatively correlating with overall patient survival and recurrence-free survival [ 90 92 ]. In addition, Toll-like receptor 4 (TLR4) stimulates IL-10 secretion through M2 macrophages [ 93 ], and therefore, TLR4 may also be a key signal that promotes alterations in the TME.…”
Section: Mechanisms Of Tumor Progression Mediated By Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…The survival of subtype 3 is significantly worse than subtype 2 may be caused by the difference in M2 macrophages infiltrates (p ≤ 0.01, Figure S6A). Studies have shown that macrophages with local infiltration can undergo M2 type polarization in the tumor microenvironment, thereby exerting immunosuppressive effects and promoting intratumoral angiogenesis, tumor proliferation, invasion, and invasion metastasis (30,31).In addition, subtypes 3 patients showed higher angiogenesis (Angiogenesis, p ≤ 0.001), pan-fibroblast TGF-b(Pan-F-TBRs, p ≤ 0.0001), and epithelial interstitial transformation (EMT, p ≤ 0.05) (Figure S6B) compared with subtypes 2, suggesting that subtypes 3 patients had more robust pro-cancer activity. which is consistent with a worse prognosis for patients (Figure 2B).…”
Section: Discussionmentioning
confidence: 99%
“…In the TME, the accumulation of cytokines, chemokines, soluble factors, and a mixture of biomolecules in exosomes compromises the immune response during the advanced stages of cancer ( 156 158 ). Soluble factors with immunosuppressant activity, such as IL-10, TGF-b, IL-4, IL-6, etc., impair the function of NK cells ( 159 , 160 ) and CTLs ( 161 , 162 ) by inhibiting their effector activity and downregulating the expression of transcripts coding for cytolytic molecules. This cytokine environment induces the differentiation of CD4+ T to Treg cells ( 163 165 ) and maintains a stage of dedifferentiation in MDSCs by enhancing the expression of TGF-β and IL-10.…”
Section: Participation Of the Immune Response In Cancermentioning
confidence: 99%